Effects of Pistacia terebinthus L. Subsp. palaestina and Rhus coriaria L. Plants on Some Biochemical Parameters of Brain Tissue of Sprague-Dawley Rats in Experimental Breast Cancer Model - Erisir, Figen Erdem; Kirecci, Oguz Ayhan; Yilmaz, Okkes; Ozsahin, Ayse Dilek (Kahramanmaras Sutcu Imam Univ Rektorlugu, 2022)
In this study, the therapeutic effects of Pistacia terebinthus L. subsp. Palaestina (terebinth) and Rhus coriaria L (sumac) plants on DMBA-induced breast cancer in 66 female Sprague-Dawley rats were investigated through biochemical analysis. The rats were divided into 6 groups as Control, DMBA (7.12-Dimethylbenzanthracene), PT (terebinth), RC (sumac), PT+DMBA and RC+DMBA. DMBA was administered to 8-week-old rats via gavage, a single dose of 80 mg/kg according to body weight. Aqueous extracts of terebinth and sumac were given orally to rats in antioxidant groups 3 days a week. In biochemical studies, changes in activities of the antioxidant enzymes CAT (catalase), GST (glutathione transferase), and SOD (superoxide dismutase) in brain tissues as well as total protein, MDA (malondialdehyde), GSH (glutathione), fatty acid, and vitamin levels were determined. Total protein levels generally reduced in the DMBA group compared to the control group (p<0.05)while the levels of the MDA in the DMBA brain tissue groups elevated compared to the control group and reduced in antioxidant groups (p<0.01; p<0.001). Cholesterol levels and lipophilic vitamins were determined by HPLC. Their grades were different in the DMBA and antioxidant groups. Fatty acids were analyzed by GC. As a result of analysis, fatty acids such as palmitic, palmitoleic, stearic, oleic, linoleic, arachidonic, and docosahexaenoic were high in the tissues examined (p<0.01; p<0.001). The fatty acid levels were also found to vary in the DMBA and antioxidant tissue groups. These data suggest that Pistacia terebinthus and Rhus coriaria plants can be used against breast cancer and to reduce its negative outcomes, and studies should be continued for their safe medical application.
Keywords: Biochemical parameters; Brain tissue; Breast cancer; Pistacia terebinthus; Rhus coriaria